Đặc điểm địa hóa khoáng vật của vỏ phong hóa khu vực quy hoạch đô thị Đông Hà (Quảng Trị) - An, Phạm Văn; Tú, Vũ Lê; Cương, Phạm An (Vietnam Journal of Earth Sciences, 2001)
Geochemical and mineral features of weathering crust of planed urban area in Dong Ha - Quang Tri province